Randomized controlled trial demonstrates the benefit of RGTA® based matrix therapy to treat tendinopathies in racing horses. - Sandrine Jacquet-Guibon; Anne-Gaelle Dupays; Virginie Coudry; Nathalie Crevier-Denoix; Sandrine Leroy; Fernando Siñeriz; Franck Chiappini; Denis Barritault; Jean-Marie Denoix (PLoS ONE, 2018)
A randomized controlled trial was performed on racing horses, to evaluate the efficacy of a new class of therapeutic agents in regenerative medicine-ReGeneraTing Agents® (RGTA®), to treat tendinopathies. Preliminary uncontrolled studies on tendon healing in racing horses with RGTA® (OTR4131)-Equitend® showed encouraging results, justifying performing a randomized, controlled, multicenter study with a two-year racing performance follow up. The objective of this study was to evaluate the effect of Equitend® versus placebo on acute superficial digital flexor tendonitis in racing French Standardbred Trotters (ST). Twenty-two ST were randomly and blindly assigned to receive with a ratio of 2 to 1, a single Equitend® (n = 14) or placebo (n = 8) intralesional injection under ultrasonographic guidance. Horses were evaluated over 4 months, by clinical and ultrasonographic evaluations (day 0, months 1, 2, 4), and their racing performances followed up over the 2 years after treatment. During the first month of treatment, a significant decrease in the cross-sectional area (CSA) was found in the Equitend® group (p = 0.04). After 4 months, the number of Equitend® treated horses with an improved CSA was significantly higher than the placebo-treated horses (p = 0.03571). The Equitend® group returned to their pre-injury performance level, racing in, and winning, significantly more races than the placebo group (p = 0.01399 and 0.0421, respectively). Furthermore, recurrence was significantly higher in the placebo group than in the Equitend® group (71.4% vs 16.6%, p = 0.02442). In conclusion, we measured a significant, short-term, reduction effect on CSA and demonstrated a long-term beneficial effect of intralesional injection of Equitend® for the treatment of superficial digital flexor tendonitis on racing ST, racing 2. 3 times more often than placebo, with 3.3 times fewer recurrences maintaining pre-injury performance level. This study may open the way for the development of a human treatment of tendonitis.